Developing a strategic model of participation in policy development for nurses - O. Wichaikhum (2020)
© 2019 International Council of Nurses Aim: To develop a strategic model of participation in policy development for nurses in Thailand. Background: Public health policies inevitably affect nursing practice, service delivery and the nursing workforce. Available evidence indicates that nurses have minimal participation in policy development. Introduction: Nurses’ participation in public health policy development is essential to developing and maintaining an efficient, high-quality healthcare system. Methods: The Delphi method was used to develop the strategic model based on the input of fifteen nurse experts who were interviewed over three Delphi rounds. Data were analysed descriptively to identify items to be retained or dropped, and the final list of statements was verified by all participants to establish the strategic model of participation. Findings: The strategic model contains twenty-five participation strategies for nurses wishing to engage with public health policy development. Within the model, the priorities as identified by clinical nurses, nurse leaders, nurse researchers and scholars, nursing educational institutions and nursing professional organizations are acknowledged. Conclusion: The model represents a consensus of values related to policy participation by nurses and the results align with similar studies. The inclusion of different nursing groups in promoting and developing strategies to participate in policy development ensures that all nurses have a role to play in developing nursing capacity for effective health policy engagement. Implication for nursing policy: Nursing involvement in policies that affect them and their practice is fundamental to establishing good public policy. This research provides a clear mechanism for the development of nurses’ awareness and abilities to become involved in policy development and review processes.